Vitamin D deficiency and adrenal function in critically Ill children - Manassawee Korwutthikulrangsri (2018)
© 2015, Journal of the Medical Association of Thailand. All rights reserved. Background: Data on interrelationship between vitamin D deficiency (VDD) and adrenal insufficiency in critically ill children are limited. Objective: To determine vitamin D status in critically ill children and its relationship with adrenal function. Material and Method: Thirty-two patients and 36 controls were included. Serum 25-hydroxyvitamin D (25-OHD) levels were measured. Pediatric Risk of Mortality (PRISM) III score, outcome and adrenal function assessed by 1-microgram adrenocorticotropic hormone test were collected. Results: Median (IQR) serum 25-OHD of the patients was less than that of the controls (16.6 (13.3-19.5) vs. 24.2 (21.0-27.9) ng/mL, p<0.001). Twenty-five (78%) patients and seven (19%) controls had VDD. PRISM III score, proportions of patients with shock and vasopressive drug used, length of intensive care unit stay and ventilator used, and adrenal function were not different between patients with and without VDD. Patients with serum 25-OHD of less than 12 ng/mL had higher median (IQR) PRISM III score (14 (6-20) vs. 5 (2-10), p = 0.033) and higher proportion of mortality than those with serum 25-OHD of 12 ng/mL or greater. Conclusion: A greater proportion of VDD in critically ill children as compared with that of the controls was demonstrated. Serum 25-OHD was not associated with adrenal function.